Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - 1.3 Complex Numbers - 1.3 Exercises - Page 112: 57



Work Step by Step

$(2+4i)(-1+3i)$ Evaluate the product by multiplying each term of the first factor by every term of the second factor: $(2+4i)(-1+3i)=-2+6i-4i+12i^{2}=...$ Substitute $i^{2}$ by $-1$ and simplify: $...=-2+6i-4i+12(-1)=-2+2i-12=-14+2i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.